Layanan Berbasis Cloud Untuk Infrastruktur Jaringan Mobile First – Iot – Cloud Native Versi Aruba - Syamsu, Muhajir; Widodo, Widodo (ITB Ahmad Dahlan Jakarta, 2021)
The presence of industry 4.0, of course, has a huge impact on various industrial sectors, whose infrastructure is now being developed with the concept of cloud-based services for Mobile Network Infrastructure First - IoT - Cloud Native which is intended for large companies, campuses and data center services. employed remotely or known as the company's network infrastructure. This study aims to determine the extent to which the network technology developed by Aruba with a Cloud service model is able to provide the enterprise segment and has the freedom to choose and run cloud-based components. This study uses qualitative methods, with a research approach to the analysis of natural object concepts, with data collection techniques, explanations from resource persons and literature with natural data and describes all technological services implemented by Aruba, and uses techniques Data analysis used in this research is to use analysis in the form of documentation in the form of writing and organize the data into categories, describing it into units. The results of this study indicate that with the presence of ARUBA with cloud-based services for Mobile Network Infrastructure First - IoT - Cloud Native is able to provide and provide various kinds of solutions and is able to provide cloud services to large companies, campus data center services so that can increase business value by using the service concept offered by Aruba.